Monetary policy and interest rates : proceedings of a conference sponsored by Banca d'Italia, Centro Paolo Baffi and the Innocenzo Gasparini Institute for Economic Research (IGIER) - Angeloni, Ignazio; Rovelli, Riccardo (Houndsmills, Basingstoke, Hampshire : Macmillan Press, 1998)
An examination for international policymakers and academics conducting monetary policy arising from a conference organized by the Banca d'Italia. The yield curve - the relation among market interest rates of different maturities - is a key benchmark for evaluating investment strategies in the global financial market. To a growing extent, central banks use it to evaluate, explain to the public and monitor the results of policy decisions.
"First published in Great Britain 1998 by Macmillan Press Ltd."
Includes bibliographical references and indexes.
oif 01/09/15, opc10/1/17
Loans
Keywords: Monetary policy; Interest rates; Europe